1982
DOI: 10.1007/bf01799754
|View full text |Cite
|
Sign up to set email alerts
|

Organic aciduria in neonatal multiple carboxylase deficiency

Abstract: A Samoan patient and a Saudi-Arabian patient were found to have abnormalities in the pattern of organic acid metabolites characteristic of 3-methylcrotonylglycinuria, propionic acidaemia and lactic acidosis. Both patients died early in life. The metabolic pattern is diagnostic of multiple carboxylase deficiency and an enzymatic diagnosis was made in a subsequent affected sibling of the first patient. Deficiency of the three carboxylases suggests a primary defect in the metabolism of biotin which is required fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Seizures have been reported as a prominent clinical feature in two of five HCSD cases (Wolf et al, 1981;Narisawa et al, 1982) and in 15 of 28 BD cases (Lehnert et al, 1979;Munnich et al, 1980;1981~;19816; Leonard et al, 1981; Thoene et al, 1981 ;Sherwood et al, 1982;Sweetman et al, 1982;Pocecco et al, 1983;Wolf et al, 19836;Diamantopoulos et al, 1984;Di Rocco et al, 1984;Fois et al, 1986;Low et al, 1986). Seizures have also been reported in an exceptional case of adult-onset form (Bressman et al, 1986) and in acquired biotin deficiency (Kien et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seizures have been reported as a prominent clinical feature in two of five HCSD cases (Wolf et al, 1981;Narisawa et al, 1982) and in 15 of 28 BD cases (Lehnert et al, 1979;Munnich et al, 1980;1981~;19816; Leonard et al, 1981; Thoene et al, 1981 ;Sherwood et al, 1982;Sweetman et al, 1982;Pocecco et al, 1983;Wolf et al, 19836;Diamantopoulos et al, 1984;Di Rocco et al, 1984;Fois et al, 1986;Low et al, 1986). Seizures have also been reported in an exceptional case of adult-onset form (Bressman et al, 1986) and in acquired biotin deficiency (Kien et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Seizures have been described as generalized (Lehnert et al, 1979; Leonard et al, 1981; Thoene et al, 1981): grand mal, myoclonic and clonic (also reported in two siblings of a propositus) (Cowan et al, 1979), tonic (Sweetman et al, 1982), and usually myoclonic . But details of EEGs and samples have not been published.…”
Section: Discussionmentioning
confidence: 99%
“…These patients, also described as having the neonatal form of multiple carboxylase deficiency (MCD), have life threatening ketoacidosis and organic acidemia (11). They have reduced activity of all biotin-dependent caboxylases: propionyl-CoA carboxylase (PCC), pyruvate carboxylase (PC), methylcrotonyl-CoA carboxylase (MCC), and acetyl-CoA carboxylase (ACC) (12)(13)(14). In these patients, the potentially lethal disruption of gluconeogenesis, fatty acid metabolism, and amino acid catabolism can be reversed with pharmacological doses of biotin.…”
mentioning
confidence: 99%
“…The patient wi th the hi ghe st Km fo r biot in (70 ti mes no rmal) pre se nte d in the fi rst fe w ho urs of life (171) and a previous sibling had died at three days of age (144). The patient wi th the hi ghe st Km fo r biot in (70 ti mes no rmal) pre se nte d in the fi rst fe w ho urs of life (171) and a previous sibling had died at three days of age (144).…”
Section: Abnormal Holocarboxylase Synthetasementioning
confidence: 99%
“…The patient wi th the hi ghe st Km fo r biot in (70 ti mes no rmal) pre se nte d in the fi rst fe w ho urs of life (171) and a previous sibling had died at three days of age (144). In two of tho se the di agnosis was base d on the pre se nce of the ch aracte ri sti c organic aci duri a in sample s studie d po stmo rte m (144). The patient wi th a Km fo r bi otin only th re e ti me s no rmal pre se nte d at ei ght mo nths of age (1 13).…”
Section: Abnormal Holocarboxylase Synthetasementioning
confidence: 99%